2017
DOI: 10.18699/vj17.253
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between some Ulva spp. by morphological, genetic and biochemical analyses

Abstract: 1 Отдел исследований морской среды национального института океанографии и рыболовства, александрия, египет 2 Отдел молекулярной биологии исследовательского института генной инженерии и биотехнологий, садатский университет, садат, египет Ульва -самая распространенная зеленая водоросль, обитающая у побережья египта. во всем мире она ис пользуется в качестве продукта питания, применяется в медицинских целях, а также идет на удобрения и фураж. в статье приводятся результаты первого иссле дования морфологических, г… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…The present investigation paid great attention to the biochemical characterization of collecting seaweeds; a high diversity of the biochemical nature of seaweeds paves the path to explore a variety of compounds in their body composition. Generally, carbohydrates represent the major biochemical component in the three seaweeds, this may be due to higher pyrocollodion content in their cell walls (Ismail and Mohamed, 2017;Mendis and Kim, 2011). The changes in the biochemical content may be spatial or temporal but dominantly attributed to water quality (Dave and Parekh, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…The present investigation paid great attention to the biochemical characterization of collecting seaweeds; a high diversity of the biochemical nature of seaweeds paves the path to explore a variety of compounds in their body composition. Generally, carbohydrates represent the major biochemical component in the three seaweeds, this may be due to higher pyrocollodion content in their cell walls (Ismail and Mohamed, 2017;Mendis and Kim, 2011). The changes in the biochemical content may be spatial or temporal but dominantly attributed to water quality (Dave and Parekh, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of molecular and morphological analyses provides a strong and more accurate way to differentiate between organisms. In addition, biochemical analyses have been proved to be effective in discrimination of different algal species (Ismail and Mohamed, 2017).…”
Section: Morphologicalmentioning
confidence: 99%
“…U. rigida can be found in Eastern Atlantic, Caribbean, India and Pacific Oceans [3]. Melton and Lopez-Bautista [4], found that U. rigida was distributed in the Gulf of Mexico and Atlantic side of the U.S.A. Ismail and Mohamed [5], studied the cell surface of Ulva spp. under a light microscope and reported that the cells were varied in sizes and shapes.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of alga species requires a combination of molecular markers and morphological structures [11]. In addition, the morphological characters of Ulva can change with impacting environmental factors and developmental stages of the alga [5]. Ulva can grow in freshwater, brackish and saline environments [12].…”
Section: Introductionmentioning
confidence: 99%